Immunoprophylaxis of Chlamydia trachomatis lymphogranuloma venereum pneumonitis in mice by oral immunization. - Cui, Z D (1989)
Groups of BALB/c mice were orally immunized with chlamydiae and challenged intranasally to determine whether oral immunization offers protection against pulmonary disease and to characterize the nature and kinetics of the chlamydial antibody response in the lung and other mucosal sites. Protection by oral immunization from chlamydial lung disease was demonstrated by lack of replication of the organism and the lack of chlamydial antigen in lung tissue. The chlamydial immunoglobulin A (IgA) antibody response was present at all body sites, reaching peak levels in the lung as well as in the serum. Classical IgA booster effect kinetics was observed after intranasal challenge, especially in the lung. Specific IgG antibody was detected at all body sites but at lower levels. Furthermore, animals immunized orally had no pneumonic process, as determined by histopathology. These studies also suggest that passively acquired specific serum IgG antibody may not significantly influence the course of mucosal replication of the organism. These observations indicate that oral immunization activating the gut-associated lymphoid tissue system gave total protection against chlamydial lung disease, suggesting migration of immunologically competent cells from the intestine to the lung.